Symbiosis Mechanisms and Model Systems - Seckbach, Joseph (Cellular Origin, Life in Extreme Habitats and Astrobiology, 2002)
Symbiosis is the fourth volume in the series Cellular Origin and Life in Extreme Habitats (COLE). Fifty experts, from over a dozen countries, review their current studies on different approaches to these phenomena. The chapters present various aspects of symbiosis from gene transfer, morphological features, and biodiversity to individual organisms sharing mutual cellular habitats. The origin of the eukaryotic phase is discussed with emphasis on cyanelles, H syntrophy, N2 fixation, and S-based symbiosis (as well as the origin of mitochondrion, chloroplast, and nucleus). All members of the three domains of life are presented for sharing symbiotic associations. This volume brings the concept of living together as 'One plus One (plus One) equals One.' The purpose of this book is to introduce the teacher, researcher, scholar, and student as well as the open-minded and science-oriented reader to the global importance of this association